The Small-Scale Fisheries Guidelines : Global Implementation - Jentoft, Svein; Chuenpagdee, Ratana; Barragán-Paladines, María José; Franz, Nicole (Springer International Publishing : Imprint: Springer, 2017)
In June 2014, FAO member-states endorsed the Voluntary Guidelines for Securing Sustainable Small-Scale Fisheries (SSF Guidelines). These Guidelines are one of the most significant landmarks for small-scale fisheries around the world. They are comprehensive in terms of topics covered, and progressive, with their foundations based on human rights and other key principles. It can be anticipated that implementing the SSF Guidelines, whether at local, national, or regional levels, will be challenging. This book contains in-depth case studies where authors discuss the extent to which the Guidelines can help improve the realities of small-scale fishing men and women globally and make their livelihoods and communities more secure. This will require policy intervention and innovation, along with contributions of civil society organizations and academia. However, most of all it will necessitate the empowerment of fishing people so that they can become active participants in decision making on matters where their well-being and human rights are at stake. By endorsing the SSF Guidelines, states have committed themselves to support and facilitate this development. This book asks whether states can successfully "walk the talk," and provides advice as to how they can do so. The collection of case studies sets the platform for an interactive dialogue space for researchers, policy makers, civil society and small-scale fishing communities to start the conversation about the monitoring and evaluation of the implementation of the SSF Guidelines at local, national, regional and global levels. An added value is that it helps add focus to our work as civil society activists involved in ensuring the application of the SSF Guidelines. Naseegh Jaffer - General Secretary, World Forum of Fisher People (WFFP) This collection offers many ways in which institutions enabling small-scale fisheries can protect and promote sustainability, food security, customary tenure, self-management, and market access, while fostering such benefits as ecosystem-based management, protected areas, incorporation of local knowledge, and poverty alleviation. You will want to put this book in the hands of policy-makers and practitioners immediately -- and for years to come. Evelyn Pinkerton - Professor, Simon Fraser University, Canada.
Keywords: Social sciences.; Sustainable development.; Environmental sociology.; Economic development.; Social change.; Poverty.; Social justice.; Human rights.; elektronické knihy; electronic books